History as a Source of Organizational Identity Creation. Issue 12 (December 2018) - Oertel, Simon; Thommes, Kirsten
We analysed the self-representation of twelve watchmaking firms located in a cluster in East Germany to understand how they apply rhetorical history to craft their identity. The findings show that there are common elements of rhetorical history that help organizations craft their identity, but there are also differences based on each firm's historical background. While some firms specifically relate their identity to their own history, others mainly employ cluster-level history, while still others may even self-construct fictional historical roots. By discussing these findings, we contribute to a better understanding of how an organization's identity is crafted and how history is utilized in such identity creation.